Combating in the threshold of emancipation: the myriad role of arab women writers to women's emancipation in the 19™ and 20™ centuries (2011)
Towards the late nineteenth and early twentieth centuries, the clamor for women's emancipation in Arab world had been a francophone overwhelmed the global world. The emergence of feminism and women's right activities in combating for women's right has co-existed with different government and Islamism. The feminists and women activists work tremendously toward liberation from the oppression to promote equitable relations between men and women. The overall goal is to establish equity within the gender without any discrimination within the family, before the law, in political participation, in the work place, in education, and public sphere. In their attempt to push their cause forward, feminists and women's rights activists adopted different Umbrellas under which they placed women's issues. The elites and educated amidst Arab women stood up to put an end to all challenges facing Arab women in Arabian peninsula like Egypt, Saudi Arabia, Qatar, Lebanon , and etc. they began to speak and forward their ordeals to different publicizing materials like newspapers, pamphlets, memos, journals and etc. and many literary movements were established as a key to liberating the 'collective consciousness' from the traditional norms that had stunted their progress. Therefore, this paper is aiming to examine the combating efforts of Arab women writers and their myriad roles towards women's liberation in nineteenth and twentieth centuries. Interestingly, this paper enunciated the Status of Arab women in pre and post modernism, and the effects of literary salons and societies in the work of Arab women writers in 19th and 20lh centuries would be elucidated for literary discourse.